Aerial survey and glyphosate-resistant weeds control before soybean seeding - Ponte, Islana Silva; Almeida, Edmilson Igor Bernardo; de Sousa, Andreza Maciel; Ribeiro, Bruna Da Silva Brito; de Sousa, Daniel Lobo; Silva, Maria Da Paz Pires; Sousa, Washington Da Silva; de Oliveira, Leonardo Bernardes Taverny; Lessa, Bruno França Da Trindade; Souza, Jarlyson Brunno Costa [UNESP] (Southern Cross Publishing, 2024)
Interference from herbicide-resistant weeds is one of the biggest impediments in soybean crops. The aim was to evaluate the spatial dynamics and weed control under glyphosate and glufosinate combinations before soybean seeding. The experiment was conducted in a striped arrangement with thirteen treatments and seven replicates. The treatments consisted in no-treatment, glyphosate, glyphosate + fomesafen, glyphosate + saflufenacil, glyphosate + diclosulam, glyphosate + imazetapir, glyphosate + flumioxazine, glyphosate + carfentrazone-ethyl, glyphosate + imazetapyr + flumioxazine, glyphosate + glufosinate, glyphosate + flumioxazine + carfentrazone, glufosinate + saflufenacil, glufosinate + flumioxazine. The weed spatial dynamic was analyzed for geostatistics methods, while weed control by conventional and UAV (Unmanned Aerial Vehicle) methods. We identified twenty weed species, representing eighteen different genera and fourteen botanical families. It's worth noting that eudicotyledonous species were the dominant group, primarily characterized by an annual life cycle and sexual reproduction. The utilization of precision agricultural methods proved highly effective in conducting weed surveys before soybean seeding. Using glyphosate alone is not recommended in fields with a history of reactive management with this herbicide. Alternatively, combining glyphosate and glufosinate with Protox-inhibitors showed outstanding control efficacy against glyphosate-resistant or glyphosate-tolerant weeds, Cenchrus echinatus, Spermacoce verticillata and Turnera subulata.
Keywords: Brazil; drone; Glycine max; herbicide action mechanisms; weed survey